2005
DOI: 10.1021/nl050513+
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Polaritons in Finite-Length Metal−Nanoparticle Chains:  The Role of Chain Length Unravelled

Abstract: While the conceptual framework for nanoplasmonic waveguides composed of a chain of noncontacting metal nanoparticles usually neglects the effects of the ends, the long-range nature of the interparticle coupling underlying the electromagnetic transport means that finite chain length can play an important role. Here, the complex energies of the plasmon-polariton modes in finite-length nanoparticle chains are calculated to ascertain the effects of chain length on the mode dispersion and the radiative contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 24 publications
9
105
0
Order By: Relevance
“…14 Theoretical analysis revealed that for both double and single column chains, the superradiant mode not only reaches an infinite chain limit for N L = 5 -10, consistent with earlier studies, 27,50,52 but also redshifts due to plasmonic interactions as well as phase retardation as L Tot increases. 50,51 As the latter effect also depends on the width of the significantly beyond what has been reported before for single particle studies.…”
Section: -52supporting
confidence: 86%
See 2 more Smart Citations
“…14 Theoretical analysis revealed that for both double and single column chains, the superradiant mode not only reaches an infinite chain limit for N L = 5 -10, consistent with earlier studies, 27,50,52 but also redshifts due to plasmonic interactions as well as phase retardation as L Tot increases. 50,51 As the latter effect also depends on the width of the significantly beyond what has been reported before for single particle studies.…”
Section: -52supporting
confidence: 86%
“…50,51 As the latter effect also depends on the width of the significantly beyond what has been reported before for single particle studies. 25,27,40,52 Our direct observation of the infinite chain limit eliminates the need to establish it through simulations. Next, we set L Tot and the width constant (Fig.…”
Section: -52mentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 3(a) show the spectral position of the lowest energy extinction peak for different disorders and chain lengths. In general, a larger N redshifts the resonance 54,56,57 while increasing the disorder acts to blueshift it. This blueshift, which is small or moderate (≲7% of the δ = 0 value), is less marked in the shorter chains.…”
Section: ■ Resultsmentioning
confidence: 96%
“…This application was first proposed by Quinten et al 9 in 1998, and since then this system has attracted a great deal of attention. Guiding, bending, splitting, [10][11][12][13] and localization 14,15 of the optical excitations of the chain, as well as the time dependent properties, 16 have been studied carefully. Important insight into guiding properties of these systems was gained after computing the dispersion relations, 10,[17][18][19][20][21][22] both for finite and infinite chains.…”
Section: Introductionmentioning
confidence: 99%